2017
DOI: 10.1103/physrevlett.119.048002
|View full text |Cite
|
Sign up to set email alerts
|

Mixing by Unstirring: Hyperuniform Dispersion of Interacting Particles upon Chaotic Advection

Abstract: We show how to achieve both fast and hyperuniform dispersions of particles in viscous fluids. To do so, we first extend the concept of critical random organization to chaotic drives. We show how palindromic sequences of chaotic advection cause microscopic particles to effectively interact at long range, thereby inhibiting critical self-organization. Based on this understanding we go around this limitation and design sequences of stirring and unstirring which simultaneously optimize the speed of particle spread… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…To obtain stronger evidence for our view mentioned in this work and deeper insight into the phenomena, further experiments, such as exploring direct visualization of the vortex configuration [52,59], as well as theoretical investigation, may be needed. We believe that the present study will stimulate similar experiments and analysis in other systems where the dynamic ordering and disordering would be observed [10,16,41,48,[60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75].…”
Section: Resultssupporting
confidence: 55%
“…To obtain stronger evidence for our view mentioned in this work and deeper insight into the phenomena, further experiments, such as exploring direct visualization of the vortex configuration [52,59], as well as theoretical investigation, may be needed. We believe that the present study will stimulate similar experiments and analysis in other systems where the dynamic ordering and disordering would be observed [10,16,41,48,[60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75].…”
Section: Resultssupporting
confidence: 55%
“…This protocol could be used to ease processing demands in applications. Of course, there are other means for evenly distributing particles in a fluid; chaotic advection has recently been proposed as another route for homogenizing a suspension 28 . The key advantage of our method is that the driving amplitude does not have to be set to a specific critical value.…”
Section: Discussionmentioning
confidence: 99%
“…In this section, we report on a variety of disordered nonequilibrium systems that are putatively hyperuniform according to numerical/experimental protocols and analyses. Specifically, we describe the hyperuniformity characteristics of ordered and disordered jammed particle systems [27, 38, 40, 42-44, 46-49, 117, 244] and absorbing-state models [52][53][54][55][56][57][58].…”
Section: Classical Nonequilibrium Systemsmentioning
confidence: 99%
“…Remarkably, it has been discovered that off criticality, "kicking" or reactivating these systems makes them more hyperuniform with exponents that are comparable to those found for MRJ packings, i.e., the structure factor tends to S (k) ∼ k in the small wavenumber limit [56], and hence they belong to class II hyperuniform systems. Interestingly, a recent numerical study has shown that chaotically driven suspensions can lead to hyperuniform states [57].…”
Section: Hyperuniformity In Absorbing-state Modelsmentioning
confidence: 99%